ANALISIS PROSES PENGECORAN DAN PERMESINAN BUSHING RODA KERETA DI GALANGAN KAPAL - Nanda Dwiguna; Akhmad Syarief (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2016)
This study aims to know the process of making brass bushing to succeed into a product along with the value of violence and roughness. Methods used include evaporative method, CO2 sand mold and method x. This research is done by first preparing tools and materials then done casting process where brass used in melted then cast into casting castings and in chill with well water. Furthermore, the machining process using a lathe with carbide chisel and engine rotation used for 590 RPM. From roughness test result after machining process got value at outside diameter of point A 2,532 μm, point B equal to 2,544 μm, point C equal to 2,673 μm, then diameter in point A equal to 1,539 μm, point B equal to 1,749 μm. For the value of hardness on the method of sand mold CO2 obtained an average value of 42 HRB, evaporative methods of 33.2 HRB and method x obtained an average value of 39.8 HRB. Fromithese results it is known that the hardness of the best bushing in this research is by the method of sand mold CO2 because it has good heat resistance and good mold density.